Penerapan Model Pembelajaran Savi dengan Teknik Permainan Ekspesi Wajah untuk Meningkatkan Keterampilan Membaca Puisi Siswa Kelas IV SDN Tegalkalong - Suryadi, Tatang; Iswara, Prana Dwija; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
This research is based on learning to read poetry by declamation which hasn't been maximized and there are still low poetry reading skills with pronunciation, intonation, and expression. One of the factors problem is that the teacher does not provide training to students. An alternative to solve these problems is by applying the SAVI learning model with face expression game techniques. This research used the Classroom Action Research method with 28 research subjects. The design research uses a model developed by Kemmis and Taggart and carried out in three cycles. Techniques for collecting data through observation of teacher and student activities, skills tests, and field notes. The results of the first cycle, 57.1% of students completed, the second cycle rose to 75%, and the third cycle to 89.3%. It can be concluded the SAVI learning model with face expression game techniques can improve poetry reading skills of students in the fourth grade of Tegalkalong Elementary School.